(untitled) (London Journal of Medical and Health Research, 2024)
Objective: To determine efficacy and tolerability of a long-acting intramuscular formulation of Vanoxerine (Vanoxerine Consta 394.2 mg) for treatment of Amphetamine-Type Stimulant (ATS) dependent patients.Design, Setting, And Participants: A 12 weeks, A multicenter, randomized, placebo-controlled trial conducted between November 2022— December 2023, at 16 Hospital-based drug clinics, in the 15 countries. Participants were 18 years or older, had Diagnostic and Statistical Manual of Mental Disorders-5 Stimulant Use Disorder Amphetamine-Type (ATS). Of the 4000 individuals screened, 3300 (82.5%) adults were randomized, 1650 participants to receive injections of Long-acting depot formulations ofVanoxerine (Vanoxerine Consta 394.2 mg) given intramuscularly once in 12 weeks and 1650 participants to receive Placebo injections, given intramuscularly once in 12 weeks.